4, 4′‐Methylene diphenyl diisocyanate (MDI) (inhalable fraction) [BAT Value Documentation, 2000]. Issue 2 (27th April 2016) - Lewalter, J.; Neumann, H.‐G.; Drexler, H.; Hartwig, A.; ,
Abstract : The German Commission for the Investigation of Health Hazards of Chemical Compounds in the Work Area has evaluated a biological tolerance value (BAT value)* for the inhalable fraction of 4, 4'‐Methylene diphenyl diisocyanate (MDI) in 1997. The evaluation of the BAT value was based on the relationship between external and internal exposure. In field studies from Lewalter and Steinmann‐Steiner‐Haldenstätt (1994), an average of 0.9 (0.6–2.0) μg MDA/g creatinine was found in the hydrolysed urine samples of 43 persons exposed to a mean MDI concentration of 3.9 (0.1–5.4) μg/m3. In a further study with a MDI exposure of 12.7 (1.8–15.3) μg/m3, an average of 2.6 (0.3–3.7) μg MDA/g creatinine was found in the hydrolysed urine of 154 persons. Consequently, no more than 11.1 μg/g creatinine and 10.2 µg/g creatinine of the corresponding MDA should be expected in the post‐shift urine after MDI exposure up to the MAK value of 50 μg/m3, respectively.On the basis of these data available, a BAT value of 10 μg 4, 4'‐diaminodiphenylmethane (after hydrolysis)/g creatinine* was evaluated. The time of sampling is important and should take place after the end of the shift at the end of the working week or shift period.When samples are taken 16 hours after the end of the shift, this corresponds to a renal excretion of 3 μg 4, 4'‐diaminodiphenylmethane (after hydrolysis)/g creatinine.